2021
DOI: 10.5713/ab.20.0585
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors improve the proliferation of Jeju black pig muscle cells by regulating myogenic differentiation 1 and growth-related genes

Abstract: Title of the manuscript: Growth factors improve the proliferation of Jeju black pig muscle cells by regulating MyoD and growth-related genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…In chicken, several studies have reported that ROH regions can harbour candidate genes associated with production traits, immune response, and environmental adaptation [ 41 , 46 , 69 , 70 ]. For the group of heavy chickens, several genes in three regions of GGA3 have been reported as candidates related to muscle growth and overlap with ROH islands detected in Italian autochthonous turkey breeds [ 71 ]: BEND6 , which was identified as a candidate gene for intramuscular fat content in chicken [ 72 ]; COL21A1 , which is regulated by growth factors and is involved in muscle growth [ 73 ]; and BMP5 , which is a strong candidate gene for body size in livestock [ 74 ]. In the group of light chickens, we identified the AFF1 gene within a ROH island on GGA4, which is known to have a lower expression level in mallards (wild ancestors with a low weight) than in Pekin ducks (large body size), and thus is related with body weight [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…In chicken, several studies have reported that ROH regions can harbour candidate genes associated with production traits, immune response, and environmental adaptation [ 41 , 46 , 69 , 70 ]. For the group of heavy chickens, several genes in three regions of GGA3 have been reported as candidates related to muscle growth and overlap with ROH islands detected in Italian autochthonous turkey breeds [ 71 ]: BEND6 , which was identified as a candidate gene for intramuscular fat content in chicken [ 72 ]; COL21A1 , which is regulated by growth factors and is involved in muscle growth [ 73 ]; and BMP5 , which is a strong candidate gene for body size in livestock [ 74 ]. In the group of light chickens, we identified the AFF1 gene within a ROH island on GGA4, which is known to have a lower expression level in mallards (wild ancestors with a low weight) than in Pekin ducks (large body size), and thus is related with body weight [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs were isolated from the femur skeletal muscle of 1-day-old male pig, following a protocol as described in our previous study [ 25 ]. The isolated MSCs were identification using flow cytometry Supplementary (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…MSCs were isolated from the femur skeletal muscle of 1-day-old male pig, following a protocol as described in our previous study [25]. After isolation, MSCs cells were cultured in Dulbecco's Modified Eagle Medium/Nutrient Mixture F-12 (DMEM/F12; Gibco, Carlsbad, CA, USA) with 15% fetal bovine serum (FBS; Gibco, Carlsbad, CA, USA) and 1% penicillin-streptomycin-glutamine (PSG; Gibco, Carlsbad, CA, USA) at a humidified atmosphere of 5% CO2.…”
Section: Msc Culture and Treatmentsmentioning
confidence: 99%
“…For animal cell cultivation, the use of commercial basal media is a common practice that ensures reproducibility and solid scientific control. these media formulations are applied in several studies with different cell types and culture protocols (Bain et al, 2013;Ho et al, 2014;cui et al, 2018;Park et al, 2021;li et al, 2021;Joo et al, 2022). the gold standard types are eagle's Minimum essential Medium (MeM) (eagle, 1959), Dulbecco's Modified eagle's Medium (DMeM) (Dulbecco & Freeman, 1959) and Ham's F-12 (Ham, 1965).…”
Section: Traditional Substrates and Media Components For Cultivated M...mentioning
confidence: 99%
“…It is also worth mentioning the presence of antibiotics or antimycotics in several media reported in cM production studies (Hong et al, 1996;Bain et al, 2013;Ho et al, 2014;Hanga et al, 2020;li et al, 2021;Joo et al, 2022;Park et al, 2021;stout et al, 2022), used in order to avoid contamination in the culture medium. For academic purposes, on a small scale, the use of antibiotics is commonplace, but for applications in the food industry this is not recommended, since the "world Health Organization strongly recommends a global reduction in the use of all classes of antibiotics of medical importance in food-producing animals".…”
Section: Traditional Substrates and Media Components For Cultivated M...mentioning
confidence: 99%